2018
DOI: 10.1111/bjd.16154
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography of basal cell carcinoma: influence of location, subtype, observer variability and image quality on diagnostic performance

Abstract: OCT is useful in the diagnosis of BCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 18 publications
5
46
0
6
Order By: Relevance
“…For the Fourier‐domain OCT type (FD‐OCT, used in 63% of all BCCs) they found a sensitivity of 93·7%, a specificity of 61·4% and a negative predictive value of 84·6%. These results are similar to a recent prospective, real‐life study evaluating the role of FD‐OCT in ‘pink’ lesions, showing a sensitivity of 96%, a specificity of 75% and a 31·8% improvement in diagnosis of BCC, compared with naked‐eye examination …”
supporting
confidence: 89%
“…For the Fourier‐domain OCT type (FD‐OCT, used in 63% of all BCCs) they found a sensitivity of 93·7%, a specificity of 61·4% and a negative predictive value of 84·6%. These results are similar to a recent prospective, real‐life study evaluating the role of FD‐OCT in ‘pink’ lesions, showing a sensitivity of 96%, a specificity of 75% and a 31·8% improvement in diagnosis of BCC, compared with naked‐eye examination …”
supporting
confidence: 89%
“…Ugyanezen tanulmányban az OCT a BCC-k szubtípusának meghatározában közel 70%ban volt eredményes. Megemlítendő, hogy ebben a tanulmányban klinikailag nem egyértelmű léziókat vizsgáltak, így a gyakorlatban ennél pontosabbnak ígérkezik a módszer (25). Az OCT 1997-es bőrgyógyászati alkalmazása óta sikertörténetnek számít a képalkotók között.…”
Section: Optikai Koherencia Tomográfiaunclassified
“…In previous studies, this could be shown using optical coherence tomography (OCT) or confocal laser scanning microscopy (RCM), when dermatoscopic findings were inconclusive. 4,5 Nevertheless, a method not being dependent on the experience of the investigator would be favorable. Spectroscopic methods such as Raman, multimodal imaging, and fluorescence methods were tested to distinguish between normal skin and skin cancer.…”
Section: Introductionmentioning
confidence: 99%